2019
DOI: 10.31234/osf.io/euqap
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of the emotional victim effect for female adult rape complainants: Does complainant distress influence credibility?

Abstract: Rape cases have a disproportionately high attrition rate and low conviction rate compared to other criminal offenses. Evaluations of a rape complainant's credibility often determine whether a case progresses through the criminal justice system. Even though emotional demeanor is not related to witness honesty or accuracy, distressed rape complainants are perceived to be more credible than complainants who present with controlled affect. To understand the extent and robustness of the influence of emotional demea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 74 publications
(95 reference statements)
0
11
1
Order By: Relevance
“…There is robust evidence for the emotional victim effect (EVE) (Ask & Landstrom 2010, Nitschke et al 2019, van Doorn & Koster 2019: Victims gain credibility by expressing negative emotion relative to expressing no emotion or positive emotion (e.g., happiness)-an effect demonstrated among both laypeople and criminal justice professionals (Nitschke et al 2019), for both physical and sexual assault victims (van Doorn & Koster 2019), and for both adult and child victims (van Doorn & Koster 2019). This bolstered credibility of an emotional witness leads to more guilty verdicts (Dahl et al 2007, Golding et al 2003, Kaufmann et al 2003) and harsher sentencing recommendations (Nadler & Rose 2003, Tsoudis & Smith-Lovin 1998.…”
Section: Victimsmentioning
confidence: 99%
“…There is robust evidence for the emotional victim effect (EVE) (Ask & Landstrom 2010, Nitschke et al 2019, van Doorn & Koster 2019: Victims gain credibility by expressing negative emotion relative to expressing no emotion or positive emotion (e.g., happiness)-an effect demonstrated among both laypeople and criminal justice professionals (Nitschke et al 2019), for both physical and sexual assault victims (van Doorn & Koster 2019), and for both adult and child victims (van Doorn & Koster 2019). This bolstered credibility of an emotional witness leads to more guilty verdicts (Dahl et al 2007, Golding et al 2003, Kaufmann et al 2003) and harsher sentencing recommendations (Nadler & Rose 2003, Tsoudis & Smith-Lovin 1998.…”
Section: Victimsmentioning
confidence: 99%
“…They are also consistent with previous studies suggesting that abusive supervision induces stress: “Such experiences of injustice may be a considerable source of stress” (Greenberg, 2004, p. 352; Mackey et al , 2017). This happens because employees expect to be fairly and respectfully treated by their supervisors and they are distressed and even shocked when they are abused by supervisors (Restubog et al , 2011; Nitschke et al , 2019). Our findings, thus, support the “resource loss cycles” corollary of the COR theory that we discussed earlier in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way that individuals are expected to convey a level of confidence that is congruent with the amount of information they possess, credible individuals are also expected to convey emotions that are congruent with the valence of the information they possess (Kaufmann et al, 2003; Nitschke et al, 2019). For example, Kaufmann et al (2003) found that mock jurors rated a rape victim as significantly more credible when she displayed negative emotions compared to when she displayed positive or neutral emotions.…”
Section: Source Credibilitymentioning
confidence: 99%